Determinants of US Inequality: Disparities Within or Between Ethnic Groups? - Oded Galor; Daniel C. Wainstock (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Is income inequality in the United States primarily driven by disparities between ethnic groups or within them? Contrary to conventional wisdom, this study uncovers a striking and transformative empirical regularity: an overwhelming 96% of contemporary inequality arises from disparities within groups sharing a common ancestral origin, dwarfing the comparatively minor contribution of inequality between groups. This extraordinary pattern persists across time, educational attainment, demographic characteristics, and geographic regions. The findings represent a shift in the empirical understanding of inequality in the United States, revealing that the deepest and most persistent economic divides run within, rather than between, ethnic communities.
Keywords: O15; Z13; D63; J15; 330; inequality; ethnicity; within group inequality; between group inequality